1998
DOI: 10.1038/sj.onc.1201929
|View full text |Cite
|
Sign up to set email alerts
|

p53 protein is activated during muscle differentiation and participates with MyoD in the transcription of muscle creatine kinase gene

Abstract: The p53 protein is a transcription factor involved in processes of cell growth and di erentiation. The muscle creatine kinase (MCK) gene whose transcription is induced during muscle di erentiation contains p53-binding sites. In this study we tested the involvement of p53 in the activation of MCK transcription during muscle di erentiation of C2 cells. We have shown that the p53 protein is stabilized and its DNA binding and transcriptional activities are induced during muscle di erentiation. At the stage of musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…A feedback mechanism, such as the known mdm2/p53 feedback loop (1), could be responsible for the subsequent transcriptional repression of p53. In fact, such a situation has been observed in several other terminally differentiated cell types such as myocytes and keratinocytes (20,26,32), in which p53 mRNA and, sometimes, protein levels are lower but the p53 activity is higher than that in precursor cells. Thus, it appears that p53 is generally activated posttranscriptionally upon differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…A feedback mechanism, such as the known mdm2/p53 feedback loop (1), could be responsible for the subsequent transcriptional repression of p53. In fact, such a situation has been observed in several other terminally differentiated cell types such as myocytes and keratinocytes (20,26,32), in which p53 mRNA and, sometimes, protein levels are lower but the p53 activity is higher than that in precursor cells. Thus, it appears that p53 is generally activated posttranscriptionally upon differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…It has been found that during C2C12 differentiation p53 shows a transient increment of stability, measurable by pulse-chase experiments, 6 and a transient surge of transcriptional activity. 5 However, we could never couple this p53 transient stability and activation with a p53-positive immunofluorescence staining (S Soddu, unpublished results).…”
Section: Dear Editormentioning
confidence: 99%
“…C2C12 myoblasts express wild-type p53 (wtp53) protein, which is activated during differentiation. 5,6 The interference with the endogenous wt-p53, by the expression of a dominantnegative p53 (dn-p53) protein, strongly inhibited terminal differentiation. 5 First, we investigated whether differentiation-associated apoptosis (DAA) and differentiation are mutually exclusive pathways, and therefore if there is the absence of simultaneous expression, in the same cell, of apoptosis and differentiation markers.…”
Section: Dear Editormentioning
confidence: 99%
“…10 In this issue, Yang et al propose a role of p53 in the activation of the myogenic differentiation checkpoint that relies on direct repression of myogenin-a MyoD downstream target gene, whose activation is required for myoblast progression toward terminal differentiation into multinucleated myotubes. 11,12 This finding is of particular interest, when considering that in unperturbed myoblasts p53 rather seems to contribute to muscle differentiation, 13,14 as it suggests that in myoblasts the activity of p53 is biased toward inhibiting differentiation by the DNA damage signaling. The authors first discovered the transcriptional repression of myogenin by p53 in the human rhabdomyosarcoma RD cell line.…”
mentioning
confidence: 98%